2019
DOI: 10.1063/1.5100342
|View full text |Cite
|
Sign up to set email alerts
|

Single-charge band-to-band tunneling via multiple-dopant clusters in nanoscale Si Esaki diodes

Abstract: The electrostatic potential of p+-n+ junctions, as in Esaki (tunnel) diodes, originates from the Coulomb potentials of ionized dopants in the depletion-layer, but it has been modeled so far based on uniform space-charge regions, ignoring the discrete and random dopant distribution. This model can explain well the band-to-band tunneling (BTBT) between the opposite bands of the quasineutral regions (conduction band in the n+-region and valence band in the p+-region). In this letter, we show that a BTBT transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It has also been reported that the phonon-assisted BTBT is preserved even in nanowire Esaki diodes [ 47 ]. In our previous work on p + n + diodes of comparable dimensions to the ones presented here, we reported that, despite the fact that quantum confinement in the thin SOI layers starts to be observed as discrete energy states, phonons are still contributing significantly to BTBT transport [ 39 , 40 ]. These results suggest that Si preserves its indirect-bandgap nature in such dimensions (still larger than 10 nm), while effects of dielectric and quantum confinement on the band nature and dopant states would be expected in much smaller scales (<10 nm) [ 48 ].…”
Section: Discussion and Outlookmentioning
confidence: 93%
See 1 more Smart Citation
“…It has also been reported that the phonon-assisted BTBT is preserved even in nanowire Esaki diodes [ 47 ]. In our previous work on p + n + diodes of comparable dimensions to the ones presented here, we reported that, despite the fact that quantum confinement in the thin SOI layers starts to be observed as discrete energy states, phonons are still contributing significantly to BTBT transport [ 39 , 40 ]. These results suggest that Si preserves its indirect-bandgap nature in such dimensions (still larger than 10 nm), while effects of dielectric and quantum confinement on the band nature and dopant states would be expected in much smaller scales (<10 nm) [ 48 ].…”
Section: Discussion and Outlookmentioning
confidence: 93%
“…Due to the early stage of this research, this work aims to highlight the fact that more experimental and theoretical analysis is certainly demanded. The results are presented first for nanoscale pn diodes, in which the depletion layers may contain QDs and discrete energy states that can work as stepping-stones for band-to-band tunneling (BTBT) transport [ 38 , 39 , 40 ]. Then, results are presented for codoped SOI-FETs, which function similarly to junctionless transistors [ 5 , 6 , 7 ], with the key difference that codoping may be more effective than single-type doping [ 41 ] for the formation of QDs, thus likely promoting single-electron tunneling (SET).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work on p + -n + diodes made on similar substrates, it was shown that the backgate could control the potential of the depletion layer and even dopant-induced energy states localized in such nanoscale depletion layers. 15,[26][27][28] In the present work, we similarly use the backgate, but reduce the dopant concentrations significantly for the p-and n-type regions by approximately two orders of magnitude: N A ≈ 1.5 × 10 18 cm −3 and N D ≈ 1.0 × 10 18 cm −3 , respectively (as estimated from four-point probe measurements of reference thicker SOI samples and supported by secondary-ion mass spectrometry measurements). Under these conditions, the pn devices were formed by overlapped doping to create a codoped region, i.e.…”
Section: Device Structure and Measurement Setupmentioning
confidence: 98%
“…On the other hand, Si BTBT devices have the advantage of CMOS compatibility, and features such as negative differential conductance (NDC), reported in Esaki (tunnel) diodes from large scale 7) to Si nanowires, 8) or negative differential transconductance (NDT), more recently reported in gated p + -i-n + devices, 9,10) are attractive for future advanced operations of Si-based electronic circuits. Such operations can include, for example, energy-efficient electronics switches, 4) logic gates with tunable carrier polarities 11,12) or multi-value logic applications based on the resonant tunneling diode mechanism 13,14) or single-charge BTBT mechanism, 15) similarly to those based on single-electron/ hole tunneling transistors. [16][17][18] In the majority of these reports, however, highly doped p + and n + Si regions are used [with concentrations well above the metal-insulator transition (MIT), known for doped bulk Si to be N D MIT ≈ 3.74 × 10 18 cm −3 for phosphorus (P) 19) and N A MIT ≈ 4.06 × 10 18 cm −3 for boron (B)].…”
Section: Introductionmentioning
confidence: 99%
“…The computational algorithm is based on coupling of adjacent P-donors ("clustering"). 27) In the algorithm, adjacent P-donors are considered as part of the same cluster if they are closer than 2r B apart (assumed here 5.0 nm). 18,20,24) The QDs must be isolated from the source and drain edges, i.e., the outermost (lead-side) P-donors in a cluster must be separated at a distance of >2r B from the left and/or right edges.…”
mentioning
confidence: 99%